Nipples, memes, and algorithmic failure: NSFW critique of Tumblr censorship - Pilipets Elena; Paasonen Susanna (United Kingdom, 2022)
In November 2018, after being suspended from Apple’s App Store for hosting child pornography, Tumblr announced its decision to ban all NSFW (not safe/suitable for work) content with the aid of machine-learning classification. The decision to opt for strict terms of use governing nudity and sexual depiction was as fast as it was drastic, leading to the quick erasure of subcultural networks developed over a decade. This article maps out platform critiques of and on Tumblr through a combination of visual and digital methods. By analyzing 7306 posts made between November 2018 (when Tumblr announced its new content policy) and August 2019 (when Verizon sold Tumblr to Automattic), we explore the key stakes and forms of user resistance to Tumblr “porn ban” and the affective capacities of user-generated content to mobilize engagement.